Proposing a training battery using adapted exercise for overweight women with cancer and its effect on weight loss: A field study in rehabilitation centers in Ain Wasara - Chettouh, Aze Dine; Chettouh, Merouane (International journal of health sciences, 2024)
Physical activity plays a crucial role in reducing obesity among cancer patients. Regular exercise has been shown to have numerous benefits for individuals undergoing cancer treatment, helping to mitigate the adverse effects of both the disease and its treatments. Here are ten key points highlighting the importance of physical activity in combating obesity in cancer patients. Weight Management: Engaging in regular physical activity is essential for maintaining a healthy weight, which is particularly important for cancer patients to reduce the risk of obesity-related complications. For example Metabolic Health: Exercise helps regulate metabolism, contributing to improved insulin sensitivity and glucose control, crucial factors in preventing and managing obesity. Muscle Mass Preservation: Physical activity aids in preserving lean muscle mass, which is often compromised during cancer treatments, helping patients maintain a healthier body composition. Improved Cardiovascular Health: Regular exercise enhances cardiovascular health, reducing the risk of heart-related issues that may arise in conjunction with obesity and certain cancer treatments.